Identification of Triazine-Resistant Vulpia bromoides - Ashworth, Michael; Han, H.; Knell, G.; Powles, S. (Weeds Science Society of America, 2016)
In Australia, triazine herbicides have routinely controlled the Vulpia species (Vulpia bromoides, Vulpia myuros, and Vulpia fasciculata; collectively referred to as silvergrass). However, a simazine-resistant silvergrass biotype, collected from Pingelly in the Western Australian grain belt in 2014, has been confirmed. Compared to the pooled mortality of three simazine-susceptible silvergrass populations (S1, S2, and S3), the simazine-resistant Pingelly population was > 594-fold resistant at the LD50 level. Dose-response screening of the simazine-selected progeny (> 800 g ai simazine ha−1) demonstrated that the simazine resistance mechanism was heritable. Sequencing of the chloroplast psbA gene revealed the resistant population is homozygous for a serine 264 to glycine mutation, which confers a high-level triazine resistance. As expected this Ser-264-Gly mutation conferred resistance to atrazine and metribuzin, but not the phenyl-urea diuron. This is the first published report confirming field-evolved triazine resistance in a Vulpia population.